Dead quiet in the hinterlands: the construction of workplace injuries in western Canadian newspapers, 2009–2014. (2nd April 2016) - Barnetson, Bob; Foster, Jason
ABSTRACT: Media reports profoundly misrepresent the nature of workplace injuries and fatalities in Canada. This study uses a new dataset comprising 409 urban and rural newspaper reports in western Canada to confirm the over-representation of fatalities, injuries to men, acute physical injuries, and injuries in blue-collar occupations found in earlier exploratory work. This misleading social construction of injuries may skew public policy and management decision-making about injury prevention. The study also confirms the existence of three key media frames: injuries are "under investigation, " "human tragedies, " and "before the court." Together, these frames cast workplace injuries as isolated events that happen to "others" for which no one is responsible (except maybe the worker), thereby suggesting that the public need not be concerned about workplace safety. Contrary to expectations, no significant differences were found between the reporting of urban and rural newspapers.